Qing Hua Chang Yin alleviates chronic colitis of mice by protecting intestinal barrier function and improving colonic microflora - Han, Yuying; Liu, Liya; Chen, Youqin; Zheng, Huifang; Yao, Mengying; Cao, Liujing; Sferra, Thomas J.; Ke, Xiao; Peng, Jun; Shen, Aling (Frontiers in Pharmacology, 2023)
Background: Qing Hua Chang Yin (QHCY) is a famous formula of traditional Chinese medicine (TCM) and has been proven to have protective effect on ulcerative colitis. However, its protective effect and potential therapeutic mechanisms in chronic colitis remain unclear. The purpose of this study is to explore the effects and underlying mechanisms of QHCY on dextran sulfate sodium (DSS)-induced chronic colitis mice model. Methods: The chronic colitis model was established by administration of 2% DSS for three consecutive cycles of 7 days with two intervals of 14 days for recovery by drinking water. The experiment lasted 49 days. The DSS + QHCY group received QHCY administration by oral gavage at doses of 1.6 g/kg/d, DSS + Mesalazine group was administrated Mesalazine by oral gavage at doses of 0.2 g/kg/d. The control and DSS group were given equal volume of distilled water. The body weight, stool consistency and blood in stool were monitored every 2 days. The disease activity index (DAI) was calculated. The colon length was measured after the mice were sacrificed. The histomorphology of colonic tissues was checked by the HE and PAS staining. Immunohistochemistry was performed to detect the expressions of pro-inflammatory cytokines (TNF-α, IL-1β and IL-6), tight junction proteins (ZO-1, occludin) and Mucin2 (MUC2). 16S rRNA sequencing analysis was conducted to study the diversity and abundance of gut microbiota changes. Results: QHCY treatment not only significantly attenuated DSS-induced the weight loss, DAI score increase, colon shortening and histological damage in mice, but also decreased the expression of pro-inflammatory cytokines in colonic tissues and increased the expression of ZO-1, occludin, and MUC2. Furthermore, QHCY enhanced the diversity of gut microbes and regulated the structure and composition of intestinal microflora in mice with chronic colitis. Conclusion: QHCY has a therapeutic effect on a murine model of chronic colitis. It can effectively reduce the clinical and pathological manifestations of colitis and prevent alterations in the gut microbiota.